A grid-tied PV-fuel cell multilevel inverter under PQ open-loop control scheme - Magdi G., Muftah; Mohamed, Salem; Yonis M Yonis, Buswig; Khlid Ben, Hamid; Doudou N., Louta; Mohamad, Kamarol (Frontiers, 2022)
This paper aims to assess the performance of a centralized single-stage grid-tied three-level diode clamped inverter connected to a PVFuel cell unit. An active and reactive power open-loop control scheme is employed to operate the inverter and achieves a current harmonic distortion below 5%. The system comprises a 150 kW/700 V PV, a 150 kW/1400 V fuel cell, a 265 kW multilevel inverter operating at a rated voltage of 415 V, and an LCL filter. Two operating scenarios are adopted to investigate the system’s responses further. In the first scenario, a local load of 509.2 kW is supplied from the PV-fuel cell inverter. The load also receives the grid’s power to meet the demand as the PV-fuel cell inverter provides only 265 kW. Whereas in the other scenario, the PV-fuel cell unit provides power to supply a local load while transporting the surplus to the grid. The results reveal the developed model’s good performance with a current harmonic distortion of 0.33%.